A Rhetorical Move Analysis of Arabic-Language Abstracts in Education and Linguistics : A Comparative Study of Native Arabic and Indonesian Speakers - Humairoh, Jasmine Afifah; Mohamad Zaka Al Farisi; Rinaldi Supriadi (Asalibuna, 2025)
Abstract writing in Arabic-language academic articles reflects culturally situated rhetorical strategies. This study investigates and compares the rhetorical structures and linguistic features of abstracts written by native Arabic speakers and Indonesian speakers in the fields of Education and Linguistics. Using a qualitative content analysis approach, 80 abstracts were analyzed based on Hyland's five-move model and Kanoksilapatham's salience theory, with a focus on tense usage (māḍī vs. muḍāriʿ) and voice (ma‘lūm vs. majhūl). The analysis reveals that Moves 1–4 are obligatory (100%) while Move 5 is conventional (96.3%). In terms of linguistic realization, ma‘lūm (39.4%) and māḍī (28.3%) were most commonly used across the corpus. Notably, Arabic writers predominantly employed māḍī (77.4%) and ma‘lūm (74.9%), whereas Indonesian writers favored muḍāriʿ (57.7%) and also showed a strong preference for ma‘lūm (79.3%). These patterns suggest that Arabic authors tend to emphasize factual reporting and authorial agency, while Indonesian authors adopt a more prospective and procedural tone. These findings highlight the impact of linguistic and cultural backgrounds on academic rhetorical preferences, with pedagogical implications for enhancing Arabic academic writing instruction for non-native speakers.   Abstrak: Penulisan abstrak dalam artikel akademik berbahasa Arab mencerminkan strategi retorika yang terletak secara budaya. Penelitian ini menyelidiki dan membandingkan struktur retorika dan fitur linguistik abstrak yang ditulis oleh penutur asli bahasa Arab dan penutur bahasa Indonesia di bidang Pendidikan dan Linguistik. Dengan menggunakan pendekatan analisis konten kualitatif, 80 abstrak dianalisis berdasarkan model lima gerakan Hyland dan teori Kanoksilapatham, dengan fokus pada penggunaan tegang (māḍī vs. muḍāriʿ) dan suara (ma‘lūm vs. majhūl). Analisis mengungkapkan bahwa Langkah 1–4 adalah wajib (100%) sedangkan Langkah 5 adalah konvensional (96,3%). Dalam hal realisasi linguistik, ma‘lūm (39,4%) dan māḍī (28,3%) paling sering digunakan di seluruh korpus. Khususnya, penulis Arab didominasi mempekerjakan māḍī (77,4%) dan ma‘lūm (74,9%), sedangkan penulis Indonesia lebih menyukai muḍāriʿ (57,7%) dan juga menunjukkan preferensi yang kuat untuk ma‘lūm (79,3%). Pola-pola ini menunjukkan bahwa penulis Arab cenderung menekankan pelaporan faktual dan agen penulis, sedangkan penulis Indonesia mengadopsi nada yang lebih prospektif dan prosedural. Temuan ini menyoroti dampak latar belakang linguistik dan budaya pada preferensi retorika akademik, dengan implikasi pedagogis untuk meningkatkan pengajaran penulisan akademik Arab untuk penutur non-asli.